Parliamentary Scrutiny of Aid Spending: The Case of the Global Challenges Research Fund. Issue 2 (8th March 2018) - Manji, Ambreena; Mandler, Peter
Abstract: This article argues that the UK is now facing an increasingly complex aid landscape and that this poses significant problems for parliamentary scrutiny. It explores one of the most important of the Official Development Assistance (ODA) innovations of recent years, the Global Challenges Research Fund (GCRF). The fund constitutes a significant investment of ODA money in research. The GCRF provides an important case study of changing aid spending. The article locates the GCRF in the wider context of UK aid over the past two decades and considers the wider parliamentary scrutiny and accountability issues to which aid-funded research gives rise.